The need for teaching games for understanding (TGfU) approach in primary physical education: A preliminary study - Balakrishnan, M.; Rengasamy, S.; Aman, M.S. (2010)
This is a preliminary study investigated the need for the Teaching Games for Understanding (TGfU) approach to be introduced to Primary Physical Education games teaching. A survey questionnaire and open ended questions were administrated to collect data on current teaching approach and the need for the TGfU as an alternative approach. Fifty eight primary school physical education teachers (21 male and 37 female) aged between 24 to 46 (SD) years responded in this study. Results indicated that 65.5 percent used a traditional teacher centered approach currently in teaching games. The findings also reported 53.5 percent of the respondents reported that all the lesson objectives could not be achieved and suggested a need for an alternative approach like TGfU in teaching games. The findings also proposed implementation of an approach that considers student interest and participation.